150k views
1 vote
Find the inverse of f(x) = -4x - 12​

1 Answer

6 votes

Answer:


\implies f^(-1)(x) =-(x)/(4)-3

Explanation:

Given :-

  • f(x) = -4x-12

And we need to find out the Inverse of the function . Let us assume that f(x) = y . Now , firstly replace x with y and vice versa.

Function :-


\implies f(x) = -4x - 12 \\\\\implies y = -4x-12

Interchanging x and y :-


\implies x = -4y - 12

Solve out for y :-


\implies x = -4y - 12 \\\\\implies -4y = x +12 \\\\\implies y =(x+12)/(-4)\\\\\implies y =-(x)/(4)-3

Replace y with f-¹(x) :-


\implies f^(-1)(x) =-(x)/(4)-3

Hence the inverse of the function is -x/4-3 .

User Martin Paucot
by
5.2k points